2010
DOI: 10.1063/1.3317406
|View full text |Cite
|
Sign up to set email alerts
|

The ground state van der Waals potentials of the strontium dimer and strontium rare-gas complexes

Abstract: The entire ground state potential energy curve of the strontium dimer is accurately described by the Tang-Toennies potential model defined by the three dispersion coefficients and two well parameters. The predicted vibrational frequency, anharmonicity, and vibration-rotation coupling constant are in excellent agreement with experiment. The Sr(2) reduced potential is almost identical to that of Ca(2) and Hg(2), providing further evidence to the conjecture that the van der Waals dimer potentials of group IIA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The 1 S 0 atomic structure means that the the outer s electrons are already paired up and therefore play a limited role in the bonding of two Sr atoms. Previous work has shown that this molecule is not deeply bound, with a well depth of D e = 1081.8 cm −1 [31,32]. Because of the large binding length and relatively larger mass of Sr atoms, the vibrational constant is fairly small, ω e = 40.3 cm −1 [32].…”
Section: A Diatomic Speciesmentioning
confidence: 85%
“…The 1 S 0 atomic structure means that the the outer s electrons are already paired up and therefore play a limited role in the bonding of two Sr atoms. Previous work has shown that this molecule is not deeply bound, with a well depth of D e = 1081.8 cm −1 [31,32]. Because of the large binding length and relatively larger mass of Sr atoms, the vibrational constant is fairly small, ω e = 40.3 cm −1 [32].…”
Section: A Diatomic Speciesmentioning
confidence: 85%
“…Energies of matrix sites (cm and co-workers, 31 where the metal -rare gas ground state interaction -was modelled using the TT empirical potential. respectively.…”
Section: Diatomicmentioning
confidence: 99%
“… a Caculated by Porsev and Derevianko (ref ). b Experimental value by Merritt et al (ref ). c Determined by Li et al (ref ). d From IPA potential of Tiesinga et al (ref ). e Determined by Yang et al (ref ). f From Fourier-transform spectroscopy by Allard et al (ref ). g Determined by Yin et al (ref ). h From Fourier-transform spectroscopy by Stein et al (ref ). i Present determination. …”
Section: Potential Energy Curves Of Alkaline Earth Dimersmentioning
confidence: 99%